Cacao Mucilage Valorisation to Produce Craft Beers: A Case Study Towards the Sustainability of the Cocoa Industry in Los Ríos Province - José Villarroel-Bastidas; Jonathan Steven Párraga-Maquilón; Cinthya Elizabeth Zapata-Zambrano; María de Guide Córdoba; Alicia Rodríguez; Alejandro Hernández; Josué Briones-Bitar (Beverages)
Cacao mucilage is a rich medium for microbial development due to the presence of various sugars, water, pectin, mineral salts, and yeasts of the Saccharomyces cerevisiae type. This study aims to provide added value to this commonly discarded residue, thereby contributing to the economic growth of the Rio Chila area in the Valencia Canton of Los Ríos Province. The methods applied for developing beer consist of malting, grinding, mashing, filtering, boiling, cooling, fermentation (during which cacao mucilage is added), and maturation, followed by physical–chemical analyses. The Fine aroma cacao mucilage presented values of 0.66% acidity, 7.63 °Brix, pH 4.43, absorbance 1.13, transmittance 23.67%, suspended solids 0.04 g: 2.66%, density 1.07 g/mL, turbidity 6.94 NTU, °GL 8.47% vol., foam quantity 1.70 cm, colorimetry L* 50.77, colorimetry a* 18.08, colorimetry b* 50.53, and bitterness degree 39.00. The analyses presented values within the normal parameters applied to beers at the national level (INEN standards). Escherichia coli, Salmonella, and total microorganisms showed no contamination in the microbiological analyses. In the sensory analyses, appearance, aroma, flavour, and mouthfeel were evaluated, with the best experiment being the combination of Fine aroma cacao with a concentration of 30% mucilage and added Cascade hops. This study took into account the concentrations of cacao mucilage (20% and 30%) from the varieties (Fine aroma and CCN-51), as well as the addition of the brewing hops Cascade and Northern Brewer. Regarding the physicochemical characteristics, adding this cacao derivative did not affect craft beer and conformed to the ranges of the NTE INEN 2262 standard. Thus, this research proposes an alternative use for cocoa mucilage, contributing to waste reduction and broadening its potential applications.